2022
DOI: 10.3390/foods11162412
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Glycerolysis of Palm Kernel Olein-Stearin Blend for Monolaurin Synthesis as an Emulsifier and Antibacterial

Abstract: Monolaurin is a monoacylglycerol, which can act as an emulsifier and antibacterial. Palm kernel oil is a monolaurin raw material that can be fractionated into palm kernel olein (PKOo) and palm kernel stearin (PKS). Therefore, this study prepares monolaurin through enzymatic glycerolysis of the PKOo-PKS blend. The effects of enzyme concentration, molar ratio of oil to glycerol, solvent to oil ratio, and reaction temperature on the products of glycerolysis were investigated. The best conditions were selected for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…This may be because the glycerolysis products contained monolaurin, which is more effective against gram-positive bacteria like B. subtilis. Meanwhile, E. coli is less sensitive against monolaurin as monolaurin has a limited effect on inhibiting the growth of gram-negative bacteria [1,11,23].…”
Section: Antibacterial Testmentioning
confidence: 99%
See 4 more Smart Citations
“…This may be because the glycerolysis products contained monolaurin, which is more effective against gram-positive bacteria like B. subtilis. Meanwhile, E. coli is less sensitive against monolaurin as monolaurin has a limited effect on inhibiting the growth of gram-negative bacteria [1,11,23].…”
Section: Antibacterial Testmentioning
confidence: 99%
“…To achieve the desired yield of glycerolysis product, these parameters need to be optimized. Ngatirah et al [11] found that he antibacterial activity of monolaurin with aquadest solvents highlights a slightest inhibitory concentration of 500 ppm for E. coli FNCC 0091 and S. aureus FNCC 0047 and 100 ppm for B. subtilis FNCC 0060. Monolaurin also affect of spore germination.…”
Section: Analysis Of Glycerolysis Productsmentioning
confidence: 99%
See 3 more Smart Citations